2020
DOI: 10.1002/lary.29253
|View full text |Cite
|
Sign up to set email alerts
|

Digital Otoscopy Videos Versus Composite Images: A Reader Study to Compare the Accuracy of ENT Physicians

Abstract: Objectives/Hypothesis With the increasing emphasis on developing effective telemedicine approaches in Otolaryngology, this study explored whether a single composite image stitched from a digital otoscopy video provides acceptable diagnostic information to make an accurate diagnosis, as compared with that provided by the full video. Study Design Diagnostic survey analysis. Methods Five Ear, Nose, and Throat (ENT) physicians reviewed the same set of 78 digital otoscope eardrum videos from four eardrum conditions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…11 Similar to still images, identifying TM retraction was challenging using those composite images. 12 Previous studies have compared the quality and reliability of video otoscopy still images or recordings with the results of different gold standards including conventional onsite otoscopy 1,7,10 or otomicroscopy. 2,3,8,13,14 Another study has compared the diagnostic accuracy and confidence using video otoscopy the enhanced composite images stitched from video otoscopy recordings collected by experienced clinicians to the original recordings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Similar to still images, identifying TM retraction was challenging using those composite images. 12 Previous studies have compared the quality and reliability of video otoscopy still images or recordings with the results of different gold standards including conventional onsite otoscopy 1,7,10 or otomicroscopy. 2,3,8,13,14 Another study has compared the diagnostic accuracy and confidence using video otoscopy the enhanced composite images stitched from video otoscopy recordings collected by experienced clinicians to the original recordings.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,8,13,14 Another study has compared the diagnostic accuracy and confidence using video otoscopy the enhanced composite images stitched from video otoscopy recordings collected by experienced clinicians to the original recordings. 12 However, no study has compared the quality and ability to view the TM using still images to those of video recordings. It is still unknown whether video otoscopy still images or recordings can improve clinician-rated quality of otoscopy for asynchronous telehealth assessments and enable a more accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“… 26 In contrast, usefulness of endoscopic videos taken by health care personnel can be limited. 25 , 118 , 148 , 149 …”
Section: Resultsmentioning
confidence: 99%
“… 81 , 109 , 118 Most studies demonstrated moderate (κ = 0.41-0.60) to substantial (κ = 0.61-0.80) diagnostic agreement between VE and FTF evaluations. 25 , 82 , 84 , 87 , 88 , 91 , 92 , 114 - 117 , 121 , 124 , 148 - 150 , 160 A major issue is the quality of the physical examination being conducted remotely, which obviously has a lot of limitations. 6 , 8 , 17 , 25 , 28 , 29 , 89 , 96 , 121 , 124 , 156 However, VE has been found to expand health coverage, prevent unnecessary visits, and save travel costs.…”
Section: Discussionmentioning
confidence: 99%
“…Another machine learning system using OCT found agreement with physician diagnosis in 91.5% of cases 25 . Manual annotations can also be automated with a machine learning frame selection tool 65 .…”
Section: Discussionmentioning
confidence: 99%